La campaña de Tudmīr - Yelo Templado, Antonio (Antigüedad y Cristianismo, 2019)
The Tudmir campaigne was one of the last that was conducted by the Ommiads Emirs against different peoples of Islamic Spain in order to supress the Mozarabic uprising that various historians have called "the nationalist movement". In Tudmir the Islamic army crushed the last rebel stronghold in the eastern regions of Al-Andalus. This represents an important chapter in the his- tory of Murcia during this period of the Dark Ages. The text of ibn-Hayyan is an exceptional islamic source and the only contemporary one extant, being one of the few remaining fragments of the famous Muqtabis. This document gives un important information about Ello in its historical context and in it appears the great personality of Daisan of Lorca, who was contemporary with and allied to Ummar ibn Hafsun.